The Role of Parents in Coping with Adolescent Aggressive Behavior - Besti Nora Dwi Putri; Rila Rahma Mulyani; Wike Wulandari (Universitas Negeri Padang, 2020)
This research is motivated by the existence of parents who do not know their role in changing adolescent aggression behavior. The purpose of this study was to describe the role of parents in overcoming children's aggressive behavior in terms of moral cultivation, development of non-aggression behavior and the cultivation of the ability to develop empathy. The research sample consisted of 36 adolescents who experienced aggressive behavior. The results of this study reveal that the role of parents in overcoming adolescent aggression behavior in general is in the sufficiently role category, meaning that parents are expected to play a greater role in overcoming the aggressive behavior of their youth so that they are able to behave in accordance with applicable norms.